Zvezdnoe nebo drevnej Mesopotamii. Šumero-akkadskie nazvanija sozvezdij i drugich svetil. - Kurtik, Gennadij E. (2007)
The Star Heaven of Ancient Mesopotamia. The Sumero-Akkadian Names of Constellations and Other Heavenly Bodies